Mouse and human embryonic genome activation initiate at the one-cell stage - Asami, Maki; Perry, Anthony C. F. (Frontiers in Cell and Developmental Biology, 2025)
At the moment of their union, fertilizing gametes (sperm and oocyte) are transcriptionally silent: gene expression has to be initiated within the resulting embryo, a process termed embryonic genome activation, EGA. Until recently, EGA was believed to occur at the two-cell stage (mouse) or four-to-eight-cell stage (human), but new evidence from single-cell RNA-sequencing (scRNAseq) suggests that it initiates at the one-cell stage in both species. Precise time-course scRNA-seq of mouse one-cell embryos revealed an EGA program referred to as immediate EGA, iEGA: iEGA occurred from within 4 h of fertilization, mainly from the maternal genome, with paternal genomic transcription from ∼10 h. Significant low-magnitude upregulation similarly occurred in healthy human one-cell embryos. In both species, new transcripts were canonically spliced, and expression predicted embryonic processes and regulatory transcription factors (TFs) associated with cancer, including MYC/c-Myc. Blocking their activities in mouse one-cell embryos induced acute developmental arrest and disrupted iEGA. Inhibiting c-Myc induced upregulation of hundreds of genes, implying that they are normatively repressed, a phenomenon we term embryonic genome repression, EGR. iEGA is downregulated coincidentally with a subsequent, higher-amplitude wave of gene expression (referred to as ‘major EGA’ or ‘major ZGA’) in two-cell (mouse) or 4–8-cell (human) embryos. We suggest that iEGA is continuous with gene expression previously termed ‘minor EGA’ (or ‘minor ZGA’) and that the regulation of iEGA and major EGA are distinctive. The pattern of gene upregulation in iEGA illuminates processes involved at the onset of development, with implications for epigenetic inheritance, stem cell-derived embryos and cancer.